Bibliometric review of actuators: Key automation technology in a smart city framework. (2022) - Rani, Sita; Kumar, Raman
Abstract: Smart cities are built in diverse mechanisms and sub-systems by integrating Information and Communication Technologies (ICT). It offers inhabitants sustainable services at a lower cost and provides full connectivity. The sensors are incorporated virtually everywhere in a smart city environment. Actuators are switching technologies that enable communication in a highly heterogeneous smart city environment and perform output functions. This article focuses on the function of actuators as a vital technology to allow different smart-city services to be automated. So, the role of actuators in the smart city was inclusively scrutinized employing bibliometric review. An organized practise was utilized to accumulate journal articles on actuators in smart cities. Screening processes have been devised for citation analyses. The utmost prolific authors, journals, articles, counties, and institutions are graded based on the overall citation count. Researching hubs and patterns were established utilizing author-keywords and index-keyword scrutiny on actuators in smart cities. The bibliometric assessment of the actuators in smart cities might deliver imperative evidence about the development of worldwide research. It is also very beneficial for upcoming researchers in the area of sensors and actuators in smart cities.